Bartleby, łowca dyskursów. O pewnej formie nie-krytyki - Szwabowski, Oskar (Kultura-Społeczeństwo-Edukacja, 2019)
In article I engage the Bartleby. His strategy, resistance and the relation to the dominant language are treats as a radical critique of discourse. Bartleby can show us a different style of critique that is coherence with paradigm of the study. My analyzed is located on the field on the philosophy of education and should be understood as developing of mentioned paradigm.